Advances in the treatment of cytomegalovirus. Issue 1 (3rd October 2019) - Krishna, B A; Wills, M R; Sinclair, J H
Abstract: Background: Human cytomegalovirus (HCMV) is a threat to immunologically weak patients. HCMV cannot yet be eliminated with a vaccine, despite recent advances. Sources of data: Sources of data are recently published research papers and reviews about HCMV treatments. Areas of agreement: Current antivirals target the UL54 DNA polymerase and are limited by nephrotoxicity and viral resistance. Promisingly, letermovir targets the HCMV terminase complex and has been recently approved by the FDA and EMA. Areas of controversy: Should we screen newborns for HCMV, and use antivirals to treat sensorineural hearing loss after congenital HCMV infection? Growing points: Growing points are developing drugs against latently infected cells. In addition to small molecule inhibitors, a chemokine-based fusion toxin protein, F49A-FTP, has shown promise in killing both lytically and latently infected cells. Areas timely for developing research: We need to understand what immune responses are required to control HCMV, and how best to raise these immune responses with a vaccine.